Masculinity and Advertisements: The Case of Nepal Television - Mishra, Indira (Crossing the Border: International Journal of Interdisciplinary Studies, 2014)
The article explores the television commercials broadcasted by the Nepal Television (NTV) that have male roles to analyze how masculinity is presented in them. In Nepal, studies of men and masculinities remain a rare compared with studies of women and femininity. It is essential to analyze the representation of masculinity to understand men’s experiences, attitudes, beliefs and practices, not only to challenge men’s superiority over females, but also to create gender equality. ! e aim of this article then is to study how a hegemonic masculinity is represented and constructed within NTV commercials. DOI: http://dx.doi.org/10.3126/ctbijis.v1i1.10463 Crossing the Border: International Journal of Interdisciplinary Studies Vol.1(1) 2013; 1-10